Implementation and challenges to preventing the re-establishment of malaria in China in the COVID-19 era - Lu, Guangyu; Cao, Yuanyuan; Zhang, Dongying; Zhang, Yuying; Xu, Yuhui; Lu, Yan; Chen, Qi; Zhu, Guoding; Yan, Jun; Müller, Olaf; Cao, Jun (Globalization and health, 2022)
The rapid emergence and global spread of COVID-19 have caused substantial global disruptions that have impacted malaria programs worldwide. Innovative strategies to enable countries aiming to eliminate malaria as well as those that are already certified as malaria-free, are needed to address malaria importation in the context of the COVID-19 pandemic. China was certified as malaria-free in 2021 and now aims to prevent the malaria re-establishment. Nonpharmaceutical interventions such as entry screening, quarantining, and health education for individuals returning from international travel during the COVID-19 pandemic present both opportunities and challenges to the management of imported malaria. This study aimed to describe and analyze the operational challenges associated with an integrated surveillance and case management program in which malaria re-establishment prevention measures were incorporated into the COVID-19 program in China.
Gesehen am 01.09.2022